SAT0548 DEVELOPMENT AND VALIDATION OF THREE PRELIMINARY MRI SACROILIAC JOINT COMPOSITE STRUCTURAL DAMAGE SCORES IN A 5-YEAR LONGITUDINAL STUDY OF PATIENTS WITH AXIAL SPONDYLOARTHRITIS. (2nd June 2020) - Wetterslev, M.; Ǿstergaard, M.; Sørensen, I. J.; Weber, U.; Loft, A. G.; Kollerup, G.; Juul, L.; Thamsborg, G.; Madsen, O.; Møllenbach Møller, J.; Juhl Pedersen, S.
Abstract : Background: In axial spondyloarthritis (axSpA), MRI reliably detects structural lesions in the sacroiliac joints (SIJs). The SPARCC SIJ Structural Score (SSS)(1) is a reliable and validated method to assess the individual structural lesions of the SIJs, i.e. fat lesion, erosion, backfill (fat metaplasia in an erosion cavity) and ankylosis. Several MRI studies have indicated that bone destruction, i.e. erosion, is often followed by formation of new bone in the erosion cavity (backfill), ultimately leading to ankylosis(2). Objectives: The aim was to combine SPARCC SSS for erosion, backfill and ankylosis into a composite score for SIJ structural damage and to test this score in a 5-year follow up study. Methods: Thirty-three patients fulfilling ASAS criteria for axSpA were followed for 5 years after initiation of TNF inhibitor in the BIOSPA study(3). T1-weighted and STIR MRI sequences of the SIJs acquired at week 0, 46 and year 2, 3, 4, 5 were evaluated with SPARCC SSS. In each of 5 slices of each SIJ, erosion is scored 0-1 per joint quadrant (score range 0-40), backfill 0-1 per joint half (score range 0-20) and ankylosis 0-1 per joint half (score range 0-20). Based on the scores for erosion, backfill and ankylosis 3 versions of a preliminary Composite axSpA MRI SIJ Structural Damage Score (CSDS) were calculated: CSDS–A: (erosion score x0.5) + backfill score + ankylosis score CSDS–B: (erosion score x1) + (backfill score x4) + (ankylosis score x6) CSDS–C: (erosion score x1) < (backfill score x4) < (ankylosis score x6) The "<" indicates a hierarchical order, meaning that erosion was not scored if backfill was present in the same joint half and erosion and backfill were not scored if ankylosis was present in the joint half. Results: Patients were divided into two groups: patients with almost complete bilateral ankylosis (baseline SPARCC SSS Ankylosis ≥18, n=10) and patients with no/minor ankylosis (baseline SPARCC SSS Ankylosis ≤7, n=23). At baseline patients with no/minor ankylosis were younger, had shorter symptom duration, lower BASMI, higher SPARCC SIJ Inflammation, lower SSS Fat, Erosion, Backfill and Ankylosis, as compared with patients with almost complete ankylosis. At baseline, CSDS-A, -B and -C correlated positively with SPARCC SSS Fat and Ankylosis and modified New York criteria grading, and negatively with BASDAI and SPARCC inflammation. Change in CSDS-B and -C over 5 years correlated positively with change in SSS Fat and Ankylosis and negatively with change in SPARCC Inflammation. There was no change in the group with almost complete ankylosis. The annual progression for CSDS-B and -C was statistically significantly larger in year 1 compared with year 4 (p=0.01) and numerically larger compared with year 2 (p=0.075), 3 (p=0.382) and 5 (p=0.073). Figure 1 shows the annual change in patients with no/minor ankylosis. Conclusion: Three preliminary Composite Structural Damage Scores for MRI assessment of the SIJs in patients with axSpA, which allows scoring of MRI progression of erosion through backfill to ankylosis, were introduced. Progression was most pronounced the first year after TNF inhibitor initiation. This novel approach may be useful for monitoring structural progression in axSpA. We suggest that these methods are further tested for responsiveness and ability to differentiate between different therapies in randomized controlled trials. References: [1]Maksymowych WP et al. J Rheum 2015;42:79-86. [2]Maksymowych WP et al. Art Rheum 2014;66:2958-67. [3]Pedersen SJ et al. Scand J Rheum 2019;48:185-197. Disclosure of Interests: Marie Wetterslev: None declared, Mikkel Ǿstergaard Grant/research support from: AbbVie, Bristol-Myers Squibb, Celgene, Merck, and Novartis, Consultant of: AbbVie, Bristol-Myers Squibb, Boehringer Ingelheim, Celgene, Eli Lilly, Hospira, Janssen, Merck, Novartis, Novo Nordisk, Orion, Pfizer, Regeneron, Roche, Sandoz, Sanofi, and UCB, Speakers bureau: AbbVie, Bristol-Myers Squibb, Boehringer Ingelheim, Celgene, Eli Lilly, Hospira, Janssen, Merck, Novartis, Novo Nordisk, Orion, Pfizer, Regeneron, Roche, Sandoz, Sanofi, and UCB, Inge Juul Sørensen: None declared, Ulrich Weber: None declared, Anne Gitte Loft Grant/research support from: Novartis, Consultant of: AbbVie, MSD, Novartis, Pfizer and UCB, Speakers bureau: AbbVie, MSD, Novartis, Pfizer and UCB, Gina Kollerup Speakers bureau: Eli Lilly, Lars Juul: None declared, Gorm Thamsborg: None declared, Ole Madsen: None declared, Jakob Møllenbach Møller: None declared, Susanne Juhl Pedersen Grant/research support from: Novartis